Dual-Antigen COVID-19 Vaccine Subcutaneous Prime Delivery With Oral Boosts Protects NHP Against SARS-CoV-2 Challenge - Gabitzsch, Elizabeth; Safrit, Jeffrey T.; Verma, Mohit; Rice, Adrian; Sieling, Peter; Zakin, Lise; Shin, Annie; Morimoto, Brett; Adisetiyo, Helty; Wong, Raymond; Bezawada, Ashish; Dinkins, Kyle; et al. (Frontiers in Immunology, 2021)
We have developed a dual-antigen COVID-19 vaccine incorporating genes for a modified SARS-CoV-2 spike protein (S-Fusion) and the viral nucleocapsid (N) protein with an Enhanced T-cell Stimulation Domain (N-ETSD) to increase the potential for MHC class II responses. The vaccine antigens are delivered by human adenovirus serotype 5 platform, hAd5 [E1-, E2b-, E3-], previously demonstrated to be effective in the presence of Ad immunity. Vaccination of rhesus macaques with the hAd5 S-Fusion + N-ETSD vaccine by subcutaneous prime injection followed by two oral boosts elicited neutralizing anti-S IgG and T helper cell 1-biased T-cell responses to both S and N that protected the upper and lower respiratory tracts from high titer (1 x 106 TCID50) SARS-CoV-2 challenge. Notably, viral replication was inhibited within 24 hours of challenge in both lung and nasal passages, becoming undetectable within 7 days post-challenge.